Tumor Neuroendócrino de pulmão em paciente acromegálico: relato de caso - Martins, Filadélfia Passos Rodrigues (2021)
Acromegaly is a rare disease, associated with multiple organs and damage to different systems. It is characterized as a hormonal disorder in which the pituitary gland (or pituitary gland) produces excess growth hormone (GH and IGF-1), causing bones and other tissues to grow beyond normal limits. The expressed case is rare and shows itself in a peculiar way, as it is associated with a large lung tumor. In this sense, the objective of this dissertation is to report the case, due to its uniqueness and to make a literature review of a neuroendocrine tumor in a patient hospitalized in January in a tertiary hospital in the city of Fortaleza with acromegaly and validating these findings with the neoplasm syndrome multiple neuroendocrine (MEN-1). The research was carried out through an expressive and exhaustive review of the literature carried out on the LILACS, Cochrane, PubMed platforms, as well as in indexed international journals or journals, allowing broad knowledge about the disease and the cases published to date. In the end, a rare event of neuroendocrine lung tumor was reported in a patient with acromegaly and pituitary macroadenoma who had clinical implications in various organs and systems. At first, the patient's chronic GH tumor hypersecretion induced skeletal deformities, metabolic disorders, complications in various organs and systems, in the situation in focus, bilateral hemianopsia, decreased libido and, finally, the signs of compression of the tumor itself, causing dyspnoea, pain and, even limiting the patient's life expectancy, which is why somatostatin analogs were started, with clinical improvement of these symptoms. The patient underwent surgery in October 2018 and showed a favorable evolution, being referred to the other center in order to undergo transfenoidal surgery in November 2018 confirming the coexistence of bronchial carcinoid and a pituitary macroadenoma, with suspicion of multiple endocrine neoplasia syndrome. type 1 (MEN-1).